Interference of the electrolyte balance and relationship on physiological variables of wool lambs submitted to heat stress - Catalano, Francisco Augusto Ricci; Bovino, Fernanda; Feitosa, Francisco Leydson Formiga [UNESP]; Pieró, Juliana Regina [UNESP]; Garcia Neto, Manoel [UNESP]; Faria Neto, Max José Araujo [UNESP]; Mendes, Luiz Claudio Nogueira [UNESP] (Medicina Veterinaria (UFRPE), 2021)
The objective of this experiment was to investigate whether manipulation of the electrolyte equilibrium of the diets, based on electrolyte balance (BE) and electrolyte ratio (RE) modifications, interfere in the response of the physiological parameters of lambs submitted to heat stress. For that, the physiological variables of twelve animals were distributed in a completely randomized experimental design, in an incomplete 3x3 factorial arrangement, totaling five treatments. The physiological variables were evaluated in three distinct periods, two of them with average temperatures of 28ºC, with an intermediate period with temperatures varying between 35 and 37ºC. The studied electrolyte balances were 0, 50 and 100 mEq kg-1 and the electrolyte ratios 5:1, 10:1 and 15:1. The results of the physiological variables were submitted to analysis of variance and later to regression analysis. The parameters: respiratory rate, heart rate, eye temperature, armpit temperature and rectal mucosal temperature were sensitive to supplementation levels of BE and or RE and were also significantly influenced (P <0.05) by ambient temperature. Thus, we can conclude that the manipulation of the electrolyte balance in sheep was able to interfere in the physiological responses of these animals.
Interferência do balanço e relação eletrolítica sobre as variáveis fisiológicas de cordeiros lanados submetidos ao estresse pelo calor
Keywords: Nutrition; Physiological variables; Sheep; Thermal stress